1992
DOI: 10.2527/1992.7041126x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated restraint and isolation stress alters adrenal and lymphocyte functions and some leukocyte differentiation antigens in lambs1

Abstract: Lambs were used to evaluate the effect of repeated restraint and isolation stress (RIS) on secretion of cortisol, lymphocyte proliferative responses to mitogens, production of interleukin-2, and expression of leukocyte differentiation antigens. Differentiation antigens evaluated included cluster of differentiation antigens 2, 4, and 8 (CD2, CD4, and CD8, respectively); B cells; and major histocompatibility complex (MHC) class II, DQ, and DR. Lambs were assigned to either control (CON; n = 12) or to RIS treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 0 publications
1
20
0
4
Order By: Relevance
“…We had anticipated either no difference in the response, or less of a response in the previously sheared ewes since wethers exposed to the same stressor every 2 wk showed less adaptation (Hargreaves and Hutson 1990d) than those repeatedly stressed on a daily basis (Minton et al 1992). Equally unexpected was the observation in this study that experienced ewes responded with much larger elevations in plasma cortisol and β-endorphin levels than naïve ewes shortly after they were exposed to the sounds, smells and sights of the shearing room.…”
Section: Hormonal Responses To Repeated Shearingmentioning
confidence: 45%
See 1 more Smart Citation
“…We had anticipated either no difference in the response, or less of a response in the previously sheared ewes since wethers exposed to the same stressor every 2 wk showed less adaptation (Hargreaves and Hutson 1990d) than those repeatedly stressed on a daily basis (Minton et al 1992). Equally unexpected was the observation in this study that experienced ewes responded with much larger elevations in plasma cortisol and β-endorphin levels than naïve ewes shortly after they were exposed to the sounds, smells and sights of the shearing room.…”
Section: Hormonal Responses To Repeated Shearingmentioning
confidence: 45%
“…There is evidence that the adrenal and immune systems of lambs adapt to stressful procedures repeated over a short time interval of several days (Minton et al 1992). A slight reduction in the stress response in lambs also occurred when stressors were repeated at 2-wk intervals (Hargreaves and Hutson 1990d).…”
Section: Mots Clésmentioning
confidence: 99%
“…Protein was measured by the Lowry method (Lowry et al 1951, Kresze 1994, and DNA determined by fluorescence bound to Hoechst 33258 (Labarca & Paigen 1980). Cortisol was measured by radioimmunoassy (RIA) (Minton et al 1992). Insulin-like growth factor (IGF)-I concentrations in plasma were measured by doubleantibody RIA after acid-ethanol cryoprecipitation (Breier et al 1993, Blum & Breier 1994.…”
Section: Assaysmentioning
confidence: 99%
“…The results showed that neither immune status of the animals in terms of peripheral leukocyte profile and lymphocyte function nor cortisol concentration was affected by the beta-agonist. Cortisol is known to be a stress hormone and has been reported to have immunosuppressive actions (Munk et al 1984), which include a) a leukocytosis with neutrophilia and eosinopenia and in some cases, lymphopenia (Collins and Suarez-Guemes 1985;Minton and Blecha 1990), b) reduced proliferation of lymphocytes in response to lectins (Coppinger et al 1991;Minton et al 1995), c) changes in the proportion of leukocytes expressing various differentiation antigens in vitro (Minton et al 1992;Cockram et al 1994). It is not surprising that the beta-agonist was not found to be immunosuppressive in the present study, as cortisol was not elevated by the beta-agonist.…”
Section: Discussionmentioning
confidence: 99%